MALARIA IN CHILDREN - Richard-Fabian Schumacher; Elena Spinelli (Mediterranean Journal of Hematology and Infectious Diseases)
This review is focused on childhood specific aspects of malaria, especially in resource-poor settings. We summarise the actual knowledge in the field of epidemiology, clinical presentation, diagnosis, management and prevention. These aspects are important as malaria is responsible for almost a quarter of all child death in sub-Saharan Africa. Malaria control is thus one key intervention to reduce childhood mortality, especially as malaria is also an important risk factor for other severe infections, namely bacteraemia. In children symptoms are more varied and often mimic other common childhood illness, particularly gastroenteritis, meningitis/encephalitis, or pneumonia. Fever is the key symptom, but the characteristic regular tertian and quartan patterns are rarely observed. There are no pathognomonic features for severe malaria in this age group. The well known clinical (fever, impaired consciousness, seizures, vomiting, respiratory distress) and laboratory (severe anaemia, thrombocytopenia, hypoglycaemia, metabolic acidosis, and hyperlactataemia) features of severe falciparum malaria in children, are equally typical for severe sepsis. Appropriate therapy (considering species, resistance patterns and individual patient factors) – possibly a drug combination of an artemisinin derivative with a long-acting antimalarial drug - reduces treatment duration to only three days and should be urgently started. While waiting for the results of ongoing vaccine trials, all effort should be made to better implement other malaria-control measures like the use of treated bed-nets and new chemoprophylaxis regimens.